2019
DOI: 10.1007/s40675-019-00148-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Links Between Social Media Use, Sleep and Mental Health: Recent Progress and Current Challenges

Abstract: Purpose of Review Sleep and mental health researchers are increasingly recognising the need to update our approaches to understanding the unique social, emotional and cognitive aspects of social media use, rather than simply considering it as just another hour of total daily "screen time". In this review, we highlight some recent developments in this area, discuss ongoing challenges facing this field and offer recommendations for future steps. Recent Findings The sleep and mental health research literatures ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 86 publications
(114 reference statements)
3
56
2
Order By: Relevance
“…15,55 This highlights the importance of uniting research that has to date largely examined social media's links to sleep and to other aspects of wellbeing or interpersonal functioning in isolation, to now move forward and build a more holistic understanding of social media's role in adolescent functioning as a whole. 21 Interestingly, our analyses highlighted individual differences in how adolescents balanced social media and sleep. Some participants reported delayed bedtimes, insufficient sleep and daytime tiredness, resulting from ongoing social media activity at nightdespite attempts to self-regulate, as has been previously documented 56 due to a sense of obligation or concern over possible exclusion.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…15,55 This highlights the importance of uniting research that has to date largely examined social media's links to sleep and to other aspects of wellbeing or interpersonal functioning in isolation, to now move forward and build a more holistic understanding of social media's role in adolescent functioning as a whole. 21 Interestingly, our analyses highlighted individual differences in how adolescents balanced social media and sleep. Some participants reported delayed bedtimes, insufficient sleep and daytime tiredness, resulting from ongoing social media activity at nightdespite attempts to self-regulate, as has been previously documented 56 due to a sense of obligation or concern over possible exclusion.…”
Section: Discussionmentioning
confidence: 82%
“…51 This highlights the value of bringing the adolescent voice to the sleep research literature, since this focus on the social interactionsrather than the devices or platforms themselvescontrasts with the prevalent "screentime" focused research often with measures that focus on the device or specific platform. 21 Furthermore, whilst adults also report feeling anxious, unpleasant and disconnected without access to their devices, 2,52 this negative experience may be particularly intense for adolescents who tend to consider social media interactions as more 'real' than older generations. 45 Efforts aiming to support adolescents in developing healthy social media habits for sleep must therefore approach bedtime social media engagement not as a form of technology use, but instead as an embedded social experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact reasons for higher TV ownership are not known; studies have shown that the popularity of "soap operas" act as cultural drivers of TV ownership in Brazil [71]. However, it indicates a media-consumption culture that is often interpreted as a compensatory response towards poor mental well-being [72,73]. In Mumbai, a recent study has shown that women feel lonely in slum rehabilitation housing (SRH), which motivates them to watch more TV and purchase more appliances as a compensatory mechanism [14].…”
Section: Appliance Ownership and Energy Culture In Slum Rehabilitatiomentioning
confidence: 99%